EVALUATION OF LENTIL GERMPLASM FOR DISEASE RESISTANCE TO FUSARIUM WILT (FUSARIUM OXYSPORUM F.SP. LENTIS) - Tzvetelina Stoilova; Peter Chavdarov (Journal of Central European Agriculture, 2006)
Lentil (Lens culinaris Medic.) is one of the oldest known protein-rich food legumes. Lentil is the second pulse crop after dry bean in Bulgaria. Diseases such as Ascochyta blight and Lentil wilt play a major role in reducing lentil yield. Thirty two lentil genotypes with different geographical origin were screened for reaction to Fusarium oxysporum f.sp. lentis during 2003-2004 from the Institute for Plant Genetic Resourses, Sadovo under greenhouse conditions. Three of the studied accessions (91-001, 91-028 and 98-001) were susceptible with 45 and 50 % of total wilted plant.